we are given
point-A= -7
point-B=8
(a)
opposite of point-A is negative of point-A value
so,
opposite of point-A is -(-7)
opposite of point-A is 7
opposite of point-B is negative of point-B value
so,
opposite of point-B is -8
opposite of point-B is -8
(b)
we can see that
opposite of point-A is 7
opposite of point-B is -8
they are not equal
so, this argument is FALSE.......Answer
7x, because 12x − 8x + 3 = 4x + 3 = 7x
12x − 5, because 12x − (8x − 3) = 12x − 5
x, because 12x − 8x + 3 = 12x − 11x = x
Answer:
A. 3 + 4x, because (12x − 8x) + 3 = 4x + 3 = 3 + 4x.
Step-by-step explanation:
12x − 8x + 3 is equal to 3 + 4x.
A.
32%
B.
33%
C.
50%
D.
83%
Answer:
63
Step-by-step explanation: